ENHANCING NEUROPLASTICITY IN POST-STROKE MOTOR RECOVERY: A SYSTEMATIC REVIEW OF THE COMPARATIVE EFFICACY OF CIMT AND MIRROR THERAPY - Ayulanda, Meiyin; Adzima, Vita Febrylia; Paramitha, Dewi Pradnya; Alya Satira; Hotma Lestari (MNJ (Malang Neurology Journal), 2026)
Background: Upper limb motor impairment is a common and often persistent consequence of stroke, significantly affecting patients' functional independence. Constraint-Induced Movement Therapy (CIMT) and Mirror Therapy (MT) have been widely utilized in post-stroke rehabilitation, yet their comparative effectiveness and neuroplastic mechanisms remains underexplored. Objective: This systematic review aimed to evaluate and compare the efficacy of CIMT, MT, and their combination in improving upper limb motor function among post-stroke patients, with a particular focus on their role in promoting neuroplasticity and neurorestoration Methods: A systematic review based on PRISMA recommendations was conducted on PubMed, ResearchGate, ScienceDirect, and ProQuest, resulting in nine eligible studies. Quality and risk of bias were assessed using the Joanna-Briggs Institute checklist. Results: A total of 248 stroke survivors participated in the reviewed studies. Outcome measures included the Fugl-Meyer Assessment (FMA), Action Research Arm Test (ARAT), Manual Function Test (MFT), and Motor Activity Log (MAL). All three interventions—CIMT, MT, and their combination—resulted in significant improvements in upper limb function compared to conventional therapy. CIMT and its variants (modified-CMIT) consistently  showed superior outcomes, particularly in patients with residual voluntary movement. Notably, combined CIMT and MT interventions demonstrated synergistic benefits in several trials. Conclusion: Both CIMT and MT are effective neurorestorative interventions for upper limb recovery after stroke, with CIMT generally producing greater improvements. CIMT primarily promotes cortical reorganization through intensive, task-specific training, whereas MT engages visuomotor and mirror neuron systems to enhance motor network activation. Their integration may provide synergistic neuroplastic benefits.